Śivarātri: Makna Perayaan Malam Śiwa - I Made Surada (Sphatika: Jurnal Teologi, 2021)
Śivarātri means the night of Śiva. Śiva is one of the manifestations of Ida Sang Hyang Widhi Waśa in its function as a reformer or fuser of everything that deserves to be fused or pralina to achieve holiness or self-awareness that gives hope for happiness.In the context of Śivarātri, of course there is Brata Śivarātri. Śivarātri brata is the main duty or firm promise to carry out the Śivarātri teachings.The day of Śivarātri has a special meaning for mankind, because on this day Sang Hyang Śiva does yoga. In this connection, Hindus carry out activities that lead to efforts to purify themselves by concentrating their thoughts before Sang Hyang in an effort to find self-awareness. This is manifested by the practice of brata in the form of upawasa, monabrata and jagra.The entry ceremony of Śivarātri which gives knowledge to humans to realize that the best human being must have sin during his life. Likewise, the ugliest human being must have been good during his life. Celebration, Śivarāri motivates every Hindu to always be aware by trying as much as possible to avoid doing prayer and always endeavoring to multiply dharma deeds.